A HUMAN RIGHTS-BASED APPROACH TO SUSTAINABLE DEVELOPMENT IN AFRICA POST- COVID-19 - Mubangizi, John Cantius (Obiter, 2024)
The worst global disaster of the twenty-first century so far, COVID-19, has caused major disruption to people’s lives and livelihoods and exposed inequalities within and among countries. Developing countries, particularly in Africa, have been hardest hit as they have had to face unprecedented challenges, with potentially extreme economic, social and sustainable development consequences. Existing challenges were worsened by COVID-19 with significant implications not only for sustainable development, but also for human rights. This article first discusses the relationship between human rights and sustainable development. The discussion then turns to the impact of COVID-19 on sustainable development with a focus on specific and relevant Sustainable Development Goals (SDGs), and on the protection and enjoyment of human rights in Africa. The article concludes by recommending a human rights-based approach as a clear and compelling direction to sustainable development in Africa in the aftermath of the devastating and unprecedented COVID-19 pandemic.